The Analysis of Regional Development on the Basis of Corporate Structures’ Activity - Gumerov, Anvar V.; Ryabinina, Elina N.; Minsabirova, Venera N.; Temirbulatov, Ruslan R.; Mitrofanova, Marina Yu.; Litvinova, Elena M.; Makhotkina, Liliia Yu.; Kharisova, Guzyal M. (International Review of Management and Marketing, 2016)
Modern conditions upgrade issues concerning the search of ways to develop and increase activity efficiency of large-scale industrial associations that possess a high concentration of material and scientific resources, and influence significantly both a certain economic sector or region and the country’s development in general. This paper aims to substantiate techniques to define the impact of corporate entities on a regional social-economic sphere. The authors have highlighted main features of Russian corporate entities and possible forms of ownership. Types of regions and their features the consideration of which is necessary to evaluate regional development are presented on the basis of the author’s estimation procedure. The factor analysis made the foundation for a rating assessment of corporate entities impact on the region; it allowed to estimate quantitatively corporations’ activity and the level of regional development at a certain time period. The paper is intended for heads of regions, top-managers, researchers dealing with issues of corporate entities’ and regional economy development. Keywords: regional economy, corporate entities, regional development, factor analysis, rating assessment JEL Classifications: Ð13, Ð’23, Ð¡58, Ð¡87